PENGARUH ELEKTRODA GRAFIT-GRAFIT, ALMUNIUM-GRAFIT, DAN SENG-GRAFIT PADA ELEKTROLISIS KOBALT (Co2+ ) DENGAN PENGOTOR ION SENG (Zn2+ ) - Wulansari, Rismita (Chem Info Journal, 2013)
A study concerning about taking cobalt metal (Co2+) has been done. The metal with drawal can be done in various method like electrowinning with electrolysis principle. This research purpose is to determine influence of electrode variation such as C-C, Al-C, and Zn-C toward precipitation of cobalt. Electrolysis cell is composed of graphite anode (C) and varieted cathode such as graphite (C), alluminium (Al), and zinc (Zn). Sample was made content of ion Co2+ and Zn2+ with electrolyte solution such as HCl for anode and without electrolyte solution for cathode, andthen both of sample was connected with KCl salt bridge. Electrolysis was done in 2,8 Volt during 40 minute with various electrode pair such as C-C, Al-C, and Zn-C. Solution from electrolysis was analysed using AAS (Atomic Absorption Spectroscopy). The result from analysis showed the decreased of Co2+ concentration before and after analysis. For electrolysis without impurities, the concentration was decreased by 105 ppm (C-C), 70 ppm (Al-C), 2and 100 ppm (Zn-C), meanwhile when electrolysis used impurities, the concentration was decreased by 85 ppm (C-C), 50 ppm (Al-C), and 70 ppm (Zn-C). The highest yield was obtained when electrolysis used C-C electrode pair which is 7,9% for electrolysis without impurities and for electrolysis with impurities the result 6,3%. The highest efficiency was obtained when electrolysis used Al-C electrode pair which is 11,7% when electrolysis without impurities and Zn-C was 23,48% when electrolysis with impurities